RUNTUHNYA DUNIA SOSIAL DI ERA KOMUNIKASI MEDIA SIMULAKRA - Naamy, Nazar (Universitas Islam Negeri Mataram, 2018)
Contemporary century humans live in the chaotic ecstasy of communication, along with the disappearance of private space. Public space is no longer a spectacle and private space is no longer a secret. The difference between the inside and the outside is erased along with the ambiguous boundary between public space and private space. The most intimate life, now a life support for virtual media. The media that support contemporary human life today have an impact on simulacra that in?uences the mind as if the virtual world of the media is real without presenting original reality essentially and fnally simulacra can control humans by trapping them to believe that simulation is real and also to make humans dependent on simulation and can’t live without it. The world like this is a concept introduced by Jean Baudrillard which represents no longer the boundary between the real and the false, so that it impacts on the collapse of human social lifebecause it is no longer able to socialize due to the media. Human life will be divided into individuals who carry out activities that they unwittingly distance from each other, and result in a lack of close relations between the people directly. So at that time human social life experienced a collapse caused by the era of media communication simulcra.